Agroforestry - the future of global land use - Garrity, Dennis; Nair, P.K. Ramachandran (Advances in Agroforestry, 2012)
Agroforestry ranks high among the significant initiatives in improving land management that have occurred the world over during the past few decades. Thanks to the global efforts in research and development during the past three decades, the age-old forms of agroforestry are being transformed from a "set of practices in search of science" to a science-based, integrated approach to addressing many of the world's most serious land-management challenges. Today, nearly a billion hectares of agricultural landscapes already have more than 10% tree cover and an estimated total of 1.6 billion hectares of land worldwide has the potential to be under agroforestry management in the foreseeable future. The World Congresses of Agroforestry (WCA), held once every five years since 2004, constitute an important set of events in the impressive development of the discipline. The second Congress (WCA2) held in Nairobi, Kenya, in 2009, was attended by about 1,200 delegates from 96 countries. This book was developed to meet the need for a volume containing such outputs that do not fit well into the thematic mode of disciplinary journals. It has been organized into three sections: the Introduction section consists of six summaries of keynote speeches at WCA2; that is followed by two sections of peer-reviewed thematic chapters grouped as "Global Perspectives" (seven chapters) and "Regional Perspectives" (11 chapters), authored by professional leaders in their respective agroforestry-related fields worldwide. A total of 130 professionals from institutions in 33 countries in both developing and the industrialized temperate regions of the world, contributed to the book as chapter authors and/or reviewers.  Thus, the book contains a solid body of the current state of knowledge on the various themes and activities in agroforestry worldwide compiled by distinguished leaders in their respective areas of expertise.